Suvremene uloge žene u obitelji iz perspektive studenata istočne Hrvatske. - Lukaš, Mirko; Puhanić, Lucija (Nova Prisutnost, 2020)
Social changes leave a great impact on the family, it's structure, factors and their family roles. Modern societies are experiencing the expansion of women in the labour market, which is reflected in their position and role in the family. In addition to the traditional role of housewife, women also take on professional engagement. In addition to her financial contribution, she continues to play the role of mother, care for children and the household in the family. The burden of most household chores remained the task of women as in previous generations. This research aimed to examine the attitudes of Eastern Croatian students about the roles of women in the modern family. The research seeks to answer which women's roles are dominant in today's families in relation to the traditional family. 375 students (202 males and 173 females) from the University in Osijek participated in the research. A survey questionnaire was used to conduct the research. Data processing was performed by descriptive statistics, t-tests for independent samples and one-way analysis of variance. The obtained results have the expected attitudes towards the role in regard to gender and field of study. Participants in social, humanities, and agrobiotechnical sciences show more egalitarian attitudes toward women's roles in the family than other participants.